The Follow the Line Method for Quran Memorisation: A Case Study of Grade 3 Students at An Indonesian Islamic Junior High School - Burhanuddin Burhanuddin; Siti Rohimah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study aims to describe the implementation and effectiveness of Quran memorization learning using the follow-the-line method for third-grade students at MTs Al-Mukmin. The research method used is a qualitative case study, using observation and in-depth interviews.semi-structured study of 13 third-grade Islamic Junior High School students who met the criteria, and documentation. The results showed that the implementation of Quran memorization learning using the